Emergence of an Escherichia coli strain co-harbouring mcr-1 and blaNDM-9 from a urinary tract infection in Taiwan. (March 2019) - Lin, Yu-Chi; Kuroda, Makoto; Suzuki, Satowa; Mu, Jung-Jung
Highlights: Analysis of a clinical E. coli strain carrying mcr-1 and bla NDM-9 by whole-genome sequencing. The mcr-1 -carrying plasmid from a human isolate is highly similar to that from a pig isolate. The bla NDM-9 gene may accelerate dissemination through distinct transmission routes. Abstract: Objectives: Multidrug-resistant bacteria have become a serious threat worldwide. In particular, the coexistence of carbapenemase genes and mcr-1 leaves few available treatment options. Here we report a multidrug-resistant Escherichia coli isolate harbouring both mcr-1 and bla NDM-9 from a patient with a urinary tract infection. Methods: Antimicrobial susceptibility and resistance genes of the E. coli isolate were characterised. Furthermore, the assembled genome sequences of mcr-1 - and bla NDM-9 -carrying plasmids were determined and comparative genetic analysis with closely related plasmids was carried out. Results: Three contigs were assembled comprising the E. coli chromosome and two plasmids harbouring mcr-1 (p5CRE51-MCR-1) and bla NDM-9 (p5CRE51-NDM-9), respectively. Whole-genome sequencing revealed that the two antimicrobial resistance genes are located on individual plasmids. Conclusions: The emergence of coexistence of carbapenemase genes and mcr-1 in Enterobacteriaceae highlights a serious threat to antimicrobial therapy.